Tindak Pidana Pencurian dalam Keadaan Memberatkan yang Dilakukan oleh Anak Berdasarkan Undang-Undang No. 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak (Studi Putusan No. 74/Pidsus Anak/2015/Pn.Blg) - Sibarani, Fianty; Lumban Gaol, Sasry A E; Fachrurrazi, Afif (JURNAL MERCATORIA, 2019)
The number of theft cases that occurred in Indonesian legal areas, especially the City of Balige, made us sad, especially the culprit is underage children. The type of research used in this Journal is normative research and is descriptive in nature. Data collection techniques are carried out by library research, namely by collecting data by conducting research on library materials. From the research it was concluded that the factors that caused the crime of theft committed by children were internal and external factors, which were internal factors including a lack of understanding of religion, family, individuals. While the external factors include environmental, economic, educational and mass media influences. Criminal law policies against criminal acts of theft in burdensome conditions committed by children receive Legal Protection Against Children Regulated in Law No. 11 of 2012 concerning Juvenile Justice, according to the author of the judge's decision in case No. 74 / Pidsus child / 2015 / Pn.Blg is not correct because it does not provide a sense of justice for the accused over considering the absence of legal assistance that should get legal assistance.